2014
DOI: 10.11607/jomi.3460
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Evaluation of Impression Techniques for Multiple Internal- and External-Connection Implant Prostheses

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 2 publications
3
26
0
1
Order By: Relevance
“…Conventional implant impressions were performed with the open tray method (Akalin et al., ; Aldosari, ; Aldosari et al., ; Amin et al., ; de Avila, de Matos Moraes, Castanharo, Del'Acqua, & de Assis Mollo, ; Bergin et al., ; Beyabanaki, Shamshiri, Alikhasi, & Monzavi, ; Buzayan, Baig, & Yunus, ; Di Fiore et al., ; Ehsani et al., ; Geramipanah, Sahebi, Davari, Hajimahmoudi, & Rakhshan, ; Ghahremanloo et al., ; Ghanem, Nassani, Baroudi, & Abdel Fattah, ; Gupta et al., ; Heidari et al., ; Lin et al., ; Marotti et al., ; Ongül et al., ; Ono et al., ; Papaspyridakos et al., ; Perez‐Davidi et al., ; Pozzi et al., ; Pujari, Garg, & Prithviraj, ; Selvaraj, Dorairaj, Mohan & Simon, ; Vigolo, Mutinelli, Fonzi & Stellini, ; Vojdani, Torabi, & Ansarifard, ; Zen et al., ), the closed tray method (Abdel‐Azim et al., ; Calesini et al., ; Del'acqua, de Avila, Amaral, Pinelli, & de Assis Mollo, ; Gökçen‐Rohlig et al., ; Ibrahim, Fouad, Elewa, & Mustafa, ; Ibrahim & Ghuneim, ; Karl et al., ; Lee et al., ; Reddy, Prasad, Vakil, Jain, & Chowdhary, ) or both the open and closed tray methods for comparison of the accuracy (Al Quran et al., ; Alikhasi, Siadat, Beyabanaki, & Kharazifard, ; Alikhasi, Siadat, & Rahimian, ; de Avila, Barros, Del'Acqua, Castanharo, & Mollo Fde, ; BalaMurugan & Manimaran, ; Chang, Vahidi, Bae, & Lim, ; Haghi, Shiehzadeh, Nakhaei, Ahrary, & Sabzevari, ; Hazboun, ; Howell et al., ; Karl & Palarie, ; Mpikos et al., ; Nakhaei, Madani, Moraditalab, & Haghi, ; Ng et al., ; Pera et al., ; Rutkunas, Sveikata, & Savickas, ; Sabouhi et al., , ; ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional implant impressions were performed with the open tray method (Akalin et al., ; Aldosari, ; Aldosari et al., ; Amin et al., ; de Avila, de Matos Moraes, Castanharo, Del'Acqua, & de Assis Mollo, ; Bergin et al., ; Beyabanaki, Shamshiri, Alikhasi, & Monzavi, ; Buzayan, Baig, & Yunus, ; Di Fiore et al., ; Ehsani et al., ; Geramipanah, Sahebi, Davari, Hajimahmoudi, & Rakhshan, ; Ghahremanloo et al., ; Ghanem, Nassani, Baroudi, & Abdel Fattah, ; Gupta et al., ; Heidari et al., ; Lin et al., ; Marotti et al., ; Ongül et al., ; Ono et al., ; Papaspyridakos et al., ; Perez‐Davidi et al., ; Pozzi et al., ; Pujari, Garg, & Prithviraj, ; Selvaraj, Dorairaj, Mohan & Simon, ; Vigolo, Mutinelli, Fonzi & Stellini, ; Vojdani, Torabi, & Ansarifard, ; Zen et al., ), the closed tray method (Abdel‐Azim et al., ; Calesini et al., ; Del'acqua, de Avila, Amaral, Pinelli, & de Assis Mollo, ; Gökçen‐Rohlig et al., ; Ibrahim, Fouad, Elewa, & Mustafa, ; Ibrahim & Ghuneim, ; Karl et al., ; Lee et al., ; Reddy, Prasad, Vakil, Jain, & Chowdhary, ) or both the open and closed tray methods for comparison of the accuracy (Al Quran et al., ; Alikhasi, Siadat, Beyabanaki, & Kharazifard, ; Alikhasi, Siadat, & Rahimian, ; de Avila, Barros, Del'Acqua, Castanharo, & Mollo Fde, ; BalaMurugan & Manimaran, ; Chang, Vahidi, Bae, & Lim, ; Haghi, Shiehzadeh, Nakhaei, Ahrary, & Sabzevari, ; Hazboun, ; Howell et al., ; Karl & Palarie, ; Mpikos et al., ; Nakhaei, Madani, Moraditalab, & Haghi, ; Ng et al., ; Pera et al., ; Rutkunas, Sveikata, & Savickas, ; Sabouhi et al., , ; ...…”
Section: Resultsmentioning
confidence: 99%
“…Impression materials were polyvinylsiloxane, vinylsiloxanether, polyether or condensation silicone. Polyvinylsiloxane materials were used in 26 studies (Abdel‐Azim et al., ; Al‐Abdullah, Zandparsa, Finkelman, & Hirayama, ; Alikhasi, Siadat, Beyabanaki et al., ; Alikhasi, Siadat, & Rahimian, ; de Avila et al., , ; BalaMurugan & Manimaran, ; Beyabanaki et al., ; Calesini et al., ; Del'acqua et al., ; Di Fiore et al., ; Ehsani et al., ; Geramipanah et al., ; Ghahremanloo et al., ; Heidari et al., ; Howell et al., ; Ibrahim et al., ; Lee et al., ; Lin et al., ; Marotti et al., ; Nakhaei et al., ; Ono et al., ; Pozzi et al., ; Sabouhi et al., ; Shim et al., ; Siadat et al., ; Zen et al., ), whereas polyether was used in 22 studies (Al Quran et al., ; Aldosari, ; Aldosari et al., ; Alikhasi, Bassir, & Naini, ; Amin et al., ; Ghanem et al., ; Hazboun, ; Ibrahim & Ghuneim, ; Karl et al., ; Martínez‐Rus et al., ; Mpikos et al., ; Ng et al., ; Ongül et al., ; Papaspyridakos et al., ; Pera et al., ; Perez‐Davidi et al., ; Rashidan, Alikhasi, Samadizadeh, Beyabanaki, & Kharazifard, ; Selvaraj et al., ; Stimmelmayr, Erdelt et al., ; Stimmelmayr, Güth et al., ; Tarib et al., ; Tsagkalidis et al., ; Vigolo et al., ), and vinylsiloxanether and condensation silicone were each used in one study (Eliasson & Ortorp, ). Sixteen studies compared any combination of the aforementioned impression materials (Akalin et al., ; Alikhasi, Siadat, Beyabanaki et al., ; Alikhasi, Siadat, & Rahimian, ; Buzayan et al., ; Chang et al., …”
Section: Resultsmentioning
confidence: 99%
“…4,7,12,15,17,20,21 This was done without considering the possible inaccuracies arising from the setting expansion of the dental stone, which may have a negative influence on positioning the laboratory analogs. In this investigation, the accuracy of 3 different impression techniques was evaluated by directly measuring the positional deviations between the implant body/impression coping before the impression procedure and the coping/laboratory analog after the impression procedure to avoid the undesirable dimensional changes and possible inaccuracies of the dental stone.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with several studies which reported the superiority of the splinted technique for internal connection implants. [11][12][13][14][15][16][17] Moreover, regarding implant angulation, 3 in vitro investigations showed that the splinted technique was more accurate than the nonsplinted technique for making an impression of angulated implants. 5,7,16 Some authors, however, have found no significant differences in the accuracy of internal connection implant impressions with the splinted and nonsplinted techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation